Three rare conditions coexisting in a proteinuric child: Questions - Agar, Buket Esen; Kara, Aslihan; Gurgoze, Metin Kaya; Dogan, Yasar; Okdemir, Deniz; Ucer, Ozlem (Springer, 2022)
[Abstract Not Available]
Keywords: Edema; Hyperglycemia; Proteinuria